Foreign indebtedness and economic growth: The Philippines - Rainer Erbe (Intereconomics, 1982)
Problems of indebtedness in developing countries are not isolated occurrences. The example of the Philippines, however, is for many reasons a most interesting one. On the one hand, borrowing already once culminated in a debt crisis at the end of the 60s. On the other, the Philippine foreign debt situation has deteriorated faster than that of other highly-indebted countries recently. This article sets out to analyse Philippine borrowing by using an econometric model against the background of the economic policies actually pursued. What are the prospects for the Philippines during the 80s?
Keywords: 330; External Debt